-10n+7=-9n-5

Simple and best practice solution for -10n+7=-9n-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10n+7=-9n-5 equation:


Simplifying
-10n + 7 = -9n + -5

Reorder the terms:
7 + -10n = -9n + -5

Reorder the terms:
7 + -10n = -5 + -9n

Solving
7 + -10n = -5 + -9n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '9n' to each side of the equation.
7 + -10n + 9n = -5 + -9n + 9n

Combine like terms: -10n + 9n = -1n
7 + -1n = -5 + -9n + 9n

Combine like terms: -9n + 9n = 0
7 + -1n = -5 + 0
7 + -1n = -5

Add '-7' to each side of the equation.
7 + -7 + -1n = -5 + -7

Combine like terms: 7 + -7 = 0
0 + -1n = -5 + -7
-1n = -5 + -7

Combine like terms: -5 + -7 = -12
-1n = -12

Divide each side by '-1'.
n = 12

Simplifying
n = 12

See similar equations:

| 2(4y-1)=6y | | 37x-21+19x=154 | | Bx+Gy=Kforx | | x+3=z-5 | | 217+x/(13.2-X)(32.8-X)=1.25 | | Ax+Fy=Kforx | | 1.25=217+x/(13.2-X)(32.8-X) | | -12n+6=-10n-2 | | 2(4a-7)+a=76 | | -37-(-43)=x/6 | | 2(4c-1)-6=3c+7 | | -7(t+1)=14 | | -7(t+1)=4 | | 1/2(18x+2)=3(3x-2)-3(x-7) | | 1/2(p+6)=7/2(3-p) | | 3x^2+(k-1)x-2=0 | | 27-19=4(x-6) | | -7x+1=9 | | 30+5y-12=17y-9-3y | | x+23+4x=-22-4x-27 | | -x(x-2)(x+2)(x+2)=0 | | b^12*b^10= | | -0.4x^2+2.2x+4.7=0 | | w^6*w^8= | | 5q^2-2bq-3=0 | | -4x+1=33 | | 2m/5+4=-10/9-3 | | P(2)-10P+22=0 | | 3(z-4)+6= | | -11/7=z-2/3 | | 2log(x-3)-log(x+1)=2 | | k*k^12= |

Equations solver categories